Exploring pedagogical potentials of technology: professional development for English teachers of vocational higher education - Lusia Eni Puspandari (Journal of Applied Studies in Language, 2023)
The education transformation from teacher centred to student centred learning has inspired most of educator to be more selective and creative to develop the way  they handle their teaching learning process. It is supported with the condition that all education must be held online due to the pandemic situation. The teachers ability in utilizing technology for their teaching learning process needs to be developed. This study aims at investigating  the teachers readiness in exploring the potential of technology in form of professional development. Modifying action research in mixed method are used as methodology in this research. Data were obtained through a focus group discussion and workshop which was followed by a semi structured interview. Findings for this study have enhanced the understanding of some aspects that teachers put into consideration while designing technology-integrated lessons; identifying goals, analysing learners, planning instructional activities, and choosing the technology tools. However, teachers must be triggered by cognitive prompts in order to support them in making decisions about learning objectives, activity stages, and technology tools to integrate.